Prospective study of hallucinations and delusions in Parkinson's disease. Issue 6 (1st June 2001) - Holroyd, S; Currie, L; Wooten, G F
Abstract : OBJECTIVE: This study was undertaken to determine the prevalence of hallucinations and delusions in Parkinson's disease, to describe such symptoms phenomenologically, and possibly to determine factors associated with their development. In addition, the role of the visual system in relation to visual hallucinations was examined. METHOD: 102 consecutive patients diagnosed with strictly defined Parkinson's disease were examined for the presence of hallucinations and delusions and assessed for visual acuity, cognition, depression using the geriatric depression scale, disease severity as measured by the UPDRS, and other clinical variables. RESULTS: Of 102 consecutive patients, 29.4% (n=30) had hallucinations or delusions, four (3.9%) were determined to be psychotic due solely to delirium and were excluded from further analysis. Of the 98 remaining patients, 26.5% (n=26) had visual hallucinations. Among these, one patient also had delusions, two had auditory hallucinations, and one had gustatory hallucinations. Visual hallucinations were significantly associated with worse visual acuity, lower cognitive score, higher depression score, and worse disease severity. Hallucinations were not associated with history of psychiatric disease, dose or duration of levodopa or other antiparkinsonian medication treatment, or duration of illness. CONCLUSIONS: Visual hallucinations are common symptoms in Parkinson's disease and are most likely of multifactorial origin. Although higher doses of levodopa are known to be related clinically to hallucinations in individual patients, the results suggest that several underlying characteristics of patients with Parkinson's disease (disease severity, dementia, depression, worse visual acuity) may be more important determinants of which patients experience hallucinations. The data also provide preliminary evidence that abnormality of the visual system may be related to visual hallucinations in Parkinson's disease, as has been found in other disorders with visual hallucinations.